Calculation method improvement of damaged elements of steel structures - G. I. Belyy; E. A. Matveev (Vestnik MGSU)
Introduction. Defects and damages of steel structures in combination with metal corrosion, stimulating the loss of local stability, can lead to their limited serviceable condition or operational unsuitability. There is no method for calculating elements with such damages. At the same time, “normative” strength testing of undamaged elements under two or more parametric loading leads to underestimated results. Therefore, the development of a reliable method for calculating the strength of elements, including undamaged ones, under general loading is relevant.Materials and methods. A method for investigating the strength of damaged and undamaged elements of steel structures in the general case of loading, taking into account the mutual influence of forces on the actual limit state corresponding to the criterion of limited plastic deformation is proposed. The solution of the problem is carried out in dimensionless parameters in reverse order, which reduces the calculation time by several orders of magnitude.Results. Based on the analysis of the obtained research results, an effective practical method for calculating damaged and undamaged elements is developed, which allows obtaining more reliable information about their strength. The effect of damage on strength was established, which, depending on its location relative to the acting forces N, Mx, My, can lead serviceable, limited or inoperable states. Significant strength reserves of undamaged I-beam elements were identified.Conclusions. An analytical solution in which the weakening of the cross section is compensated by equivalent loading by fictitious forces, allowing to reduce the strength test as for an undamaged element. The discovered strength reserves of undamaged I-beam elements indicate the need to study the rods with other types of cross sections.